2022
DOI: 10.1111/cen.14851
|View full text |Cite
|
Sign up to set email alerts
|

Serum GDF9 and BMP15 as potential markers of ovarian function in women with and without polycystic ovary syndrome

Abstract: Objective Growth differentiation factor‐9 (GDF9) and bone morphogenetic protein‐15 (BMP15) are critical paracrine regulators of female fertility and are predominantly expressed by oocytes. However, it is unknown if serum concentrations reflect changes in ovarian function and/or reproductive endocrine disorders. This study aimed to determine if serum GDF9/BMP15 are associated with ovarian, pituitary, oestrogenic, androgenic and metabolic characteristics and the ovarian pathologies, polycystic ovarian morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…showed that serum and follicular fluid BMP-15 but not GDF-9 decreased with the age of the female [19]. Another study showed a significant positive correlation between GDF-9 and female age [25].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…showed that serum and follicular fluid BMP-15 but not GDF-9 decreased with the age of the female [19]. Another study showed a significant positive correlation between GDF-9 and female age [25].…”
Section: Discussionmentioning
confidence: 93%
“…The levels of both factors in the follicular fluid can be used to determine the quality (maturity) of the oocytes retrieved following stimulation. The novelty of our study is that previous researches studied serum concentrations of BMP15 and GDF9 during the in vitro fertilization (IVF) in women with reproductive pathologies and in women with PCOS and their relations to the number of produced oocytes [18,19]. Besides, others studied the correlations of serum, follicular fluid GDF-9 and BMP-15 concentration and ICSI outcome represented by oocytes, embryos number, their qualities and chemical pregnancy rate [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that increased GDF9 levels in FF are significantly correlated with oocyte maturation and embryo quality [ 12 , 13 ], suggesting a potential relationship between GDF9 levels and oocyte competence. GDF9 was an important biomarker for predicting oocyte development potential [ 14 ]. The FF and CCs are by-products of in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) which can reflect the ovarian microenvironment to a certain extent and directly reflect the oocyte metabolism and quality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growth differentiation facor9 (GDF9) and bone morphogenetic protein15 (BMP15) are essential proteins secreted by oocytes in the primary follicle, playing a crucial role in organizing the surrounding granulosa and theca cells into the oocyte-cumulus-follicle complex. These two factors are also associated with cumulus cell proliferation, apoptosis, metabolism, and expansion, which are fundamental for embryo developmental competency and female fertility (D'Occhio et al, 2020;Alama et al, 2013;D' Occhio et al, 2020;Riepsamen et al, 2023). Consequently, GDF9 and BMP15 have become valuable markers used to assess oocyte quality and competency in recent research (Gong et al, 2021;Kousheh et al, 2022;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%